Transcriptome Sequencing Reveals a Complete Genome Sequence of Cowpea Aphid-Borne Mosaic Virus from Passion Fruit in Kenya - Munguti, F.; Maina, S.; Nyaboga, E.N.; Kilalo, D.; Kimani, E.; Macharia, M.; Holton, T.A. (American Society for Microbiology, 2019)
Analysis of transcriptome sequencing (RNA-Seq) data revealed a complete Cowpea aphid-borne mosaic virus (CABMV) genome from virus-infected passion fruit in Kenya. We compared it with six complete CABMV genomes, one each from Zimbabwe and Uganda and two each from Brazil and India.